DYNAPENIA IN ADMITTED AND NON-ADMITTED PATIENTS OLDER THAN 65 YEARS (Cuestiones de Fisioterapia, 2020)
Introduction: dynapenia is the loss of muscle strength associated with age that is not caused by neurological or muscular diseases. It predisposes to an increased risk of functional limitations and mortality. Objective: to des-cribe the frequency of dynapenia in admitted and non-admitted patients over 65 years old and to evaluate its as-sociation with sociodemographic variables, lifestyle, functional scales and hospital admission. Material and method: cross-sectional analytical study that includes 60 patients over 65 years old (30 admitted in the hospital and 30 non-admitted that were attending sessions in the Physiotherapy room). As a dependent variable, the muscle strength in the dominant hand quantified by hydraulic dynamometry and as independent variables: sociodemo-graphic and clinical variables, HARP scale, institutionalization, Barthel scale, Charlson abbreviated questionnaire,polymedication, physical activity level and daily water intake. Results: 42 women (70 %) and 18 men (30 %) were studied. The mean age was 77.5 years (IR 71.25-85,00 years), 83.3 % of those admitted and 56.7 % of the non-admitted presented dynapenia. The variables associated with dynapenia were: age (p = 0.037), hospital admission (p = 0.024), admission days (p = 0.04), Harp scale (p = 0.028), Barthel scale (p = 0.003) and physical activity (p = 0.0018).Only hospital admission (OR 4.21 CI 95 %: 1.17-16.10) and sedentary lifestyle (OR 0.23 CI 95 %: 0.06-0.79) were associated with dynapenia in multivariate analysis. Conclusions: a high prevalence of dynapenia is observed in pa-tients over 65. Hospital admission and sedentary lifestyle are independently associated with dynapenia.